Organizational psychosocial hazard exposures in UK policing: Management Standards Indicator Tool reference values - Houdmont, Jonathan; Kerr, Robert; Randall, Raymond (Emerald, 2012)
Purpose: There is a paucity of contemporary evidence on the organizational (as opposed to operational) psychosocial hazard (OPH) exposures of UK police officers. The purpose of this study is to report on OPH exposures measured via an instrument developed by the UK government - the Management Standards Indicator Tool - among police officers sampled from an entire UK force. The study provides reference values for UK police officers’ OPH exposures, considers these in relation to government exposure targets, and examines the association between officers’ OPH exposures and perceived work-related stress. Design/methodology/approach: Police officers (n = 1,729) completed the Management Standards Indicator Tool which measures perceived exposure to seven psychosocial work environment dimensions: demands, control, managerial support, peer support, relationships, role, and change. In addition, a single-item measure of perceived work-related stress was applied. Findings: Sector-specific reference values were generated by job role and rank on each of the seven dimensions assessed by the Indicator Tool. Scores on all seven dimensions were below government target levels (indicating that scores fell below the 80th percentile in relation to benchmark data). 46% of police officers reported their work to be very or extremely stressful. A significant positive correlation (p < .01) was found between scores on each of the seven psychosocial work characteristics and perceived work-related stress. Originality/value: This study is the first to report on the assessment of UK police officers’ OPH exposure using the Management Standards Indicator Tool. It provides reference values that UK forces will find useful for benchmarking and intervention-targeting purposes, and against which progress in reducing OPH exposures can be assessed.